Validation of definitions for active inflammatory lesions detected by magnetic resonance imaging in the spine of patients with spondyloarthritis - Susanne J. Pedersen (2018)
Objective. Assessment of active inflammatory features of spondyloarthritis (SpA) on magnetic resonance imaging (MRI) is of diagnostic and prognostic significance. Further study requires standardization and application of rigorous definitions of the spinal changes observed on MRI. The Canada/Denmark MRI working group has developed a comprehensive list of definitions for active inflammatory spinal lesions. We aimed to conduct a systematic evaluation of the frequency and reliability of detection of active inflammatory lesions as defined by the working group. Methods. Four readers independently recorded dichotomously (present/absent) active inflammatory lesions from lower C2 to the upper sacrum of the spine on STIR MRI scans of 20 patients with ankylosing spondylitis. All lesions were recorded at individual spinal levels except for facet joint lesions, which were recorded according to affected spinal segments. Prior to the exercise, a series of reference images were developed in which active inflammatory lesions were assigned by consensus. Frequency data were analyzed descriptively, while reliability was assessed by Cohen's unweighted kappa and percentage agreement. Results. Interobserver reliability of vertebral corner inflammatory lesions (CIL) varied substantially between reader pairs and between spinal segments. It was overall less than adequate (kappa < 0.60) for most reader pairs, although the most experienced reader pair achieved good reliability (kappa = 0.68). Reliability was fair to good for lateral segment inflammatory lesions (LIL) and non-corner inflammatory lesions (NIL) (mean kappa for experienced reader pair 0.58 and 0.66, respectively). Conclusion. Detection of CIL, LIL, and NIL was only satisfactory with the most experienced MRI reader pair. Despite rigorous standardization of definitions, detection of active inflammatory lesions is difficult and requires substantial calibration. The Journal of Rheumatology Copyright © 2009. All rights reserved.